Russian Masculinities in History and Culture
IX, 242 p.
Keywords: From the romantic liaisons of Peter the Great to the birth of the Russian 'queen', this collection of essays presents recent research from the new field of Russian masculinity studies. Peasant patriarchs, aristocratic dandies, anxious young bureaucrats, workers in search of father figures, heroic warriors, promiscuous bathhouse attendants and vodka-soaked athletic stars populate this volume. Its essays take as a starting point the notion that masculinity, like femininity, has a history.